The Effect of Cinnamon Aromatherapy in Reducing Primary Dysmenorrhea Among Adolescent Girls: A Quasi-Experimental Study - Tia Nurhanifah; Desi Soraya; Anifatus Sa’adah (Poltekkes Kemenkes Palu, 2026)
Background: Primary dysmenorrhea is a common gynecological condition affecting adolescent girls, often characterized by moderate to severe menstrual pain that disrupts daily activities and reduces quality of life. The prevalence of primary dysmenorrhea among adolescents is reported to be as high as 75%. Although pharmacological interventions such as nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used, concerns about side effects and accessibility have encouraged exploration of alternative, non-pharmacological approaches. Aromatherapy using cinnamon, which contains active compounds such as cinnamaldehyde and eugenol, has demonstrated antispasmodic and anti-inflammatory properties, making it a promising candidate for pain management. This study aimed to evaluate the effectiveness of cinnamon aromatherapy in reducing pain associated with primary dysmenorrhea among adolescent girls. Methods: A quasi-experimental design with a pretest-posttest one-group approach was used. 70 high school students in SMA Kesatrian 1 Central Java, Indonesia, who experienced primary dysmenorrhea were selected through total sampling. Participants received cinnamon aromatherapy via inhalation for three consecutive days during menstruation. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test following a normality check via the Kolmogorov–Smirnov test. Results: A significant reduction in pain intensity was observed following the intervention (Z = -6.679, p < 0.001), before the intervention, 36 female adolescents (51.4%) experienced moderate dysmenorrhea. After the intervention, 37 female adolescents (52.9%) experienced mild primary dysmenorrhea. Conclusion: Cinnamon aromatherapy effectively reduces menstrual pain and can be considered a non-pharmacological alternative for managing primary dysmenorrhea in adolescents.